Jurisprudence for Resolving Crimes of Narcotics Abuse by Children in Indonesia - Gatot Eko Yudhoyono; Eko Soponyono (Jurnal Jurisprudence, 2024)
ABSTRACT Objectives: This study aims to analyze the application of diversion in Indonesia in the process of resolving narcotics crime cases against children. It is expected that resolution through the diversion method based on the concept of restorative justice can be regulated in more detail in Act No. 35 of 2009 concerning Narcotics as a legal source in handling criminal cases in Indonesia. Methodology: This normative legal research employed a jurisprudential approach (legal products formed from judges' decisions) and laws to analyze problems, which were discussed using legal regulations in the form of secondary data (primary, secondary, and tertiary legal materials). The analysis was carried out qualitatively, and the discussion of the problem formulation used literature studies and decision documents issued by the court. Findings: Settlement of criminal cases based on the concept of restorative justice at the level of law enforcement in the police, prosecutor's office, and courts can reduce the backlog of cases and achieve legal justice as desired by the community. The court ruling of diversion in cases Number 20/Pid.Sus-Anak/2018/PN Trg, Number 2/Pid.Sus-Anak/2020/PN Trg, Number 3/Pid.Sus-Anak/2020/PN Trg, and Number 11/ Pid.Sus-Anak/2020/PN Trg at the Tenggarong District Court provided remedies to the parties in the cases based on Act No. 11 of 2012 concerning the Juvenile Criminal Justice System and Act No. 35 of 2009 concerning Narcotics. Based on the findings of the judge's judgment, it was found that the aim of implementing the Juvenile Criminal Justice System is to jointly seek a fair solution by emphasizing restoration to the original condition and not retaliation. Benefits: The government needs to create a comprehensive legal basis to regulate the process of resolving cases of narcotics abuse in children based on restorative justice simultaneously and integrated in the future reform of Narcotics Law in Indonesia. Novelty: The latest legal basis for the process of resolving narcotics abuse cases based on restorative justice is linked to Act No. 11 of 2012 concerning the Juvenile Criminal Justice System and Act No. 35 of 2009 concerning Narcotics. Based on these provisions, further discussion regarding the process of resolving criminal cases based on the concept of restorative justice by providing diversion determinations to children is discussed. Keywords: Abuse, Narcotics, Restorative Justice, and Children   ABSTRAK  Tujuan: Menganalisis penerapan diversi di Indonesia dalam proses penyelesaian perkara tindak pidana narkotika terhadap anak. Penyelesaian melalui metode diversi berbasis konsep keadilan restoratif diharapkan dapat diatur secara lebih rinci di dalam Undang-Undang No.35 Tahun 2009 tentang Narkotika sebagai sumber hukum dalam menangani perkara pidana di Indonesia. Metodologi: Penelitian ini termasuk penelitian hukum normatif dengan menggunakan pendekatan jurisprudensi (produk hukum yang terbentuk dari  keputusan hakim) dan undang-undang untuk menganalisis permasalahan yang akan dibahas menggunakan peraturan hukum berupa data sekunder (bahan hukum primer, sekunder dan tersier). Analisis dilakukan secara kualitatif dan pembahasan atas rumusan masalah menggunakan studi kepustakaan dan dokumen penetapan yang dikeluarkan oleh pengadilan. Temuan: Penyelesaian perkara pidana berbasis konsep keadilan restoratif pada tingkat penegakan hukum di kepolisian, kejaksaan dan pengadilan dapat mengurangi penumpukan perkara dan mewujudkan keadilan hukum sebagaimana diinginkan lingkungan masyarakat. Penetapan diversi, dalam perkara Nomor 20/Pid.Sus-Anak/2018/PN Trg, Nomor 2/Pid.Sus-Anak/2020/PN Trg, Nomor 3/Pid.Sus-Anak/2020/PN Trg dan Nomor 11/Pid.Sus-Anak/2020/PN Trg di Pengadilan Negeri Tenggarong. Memberikan pemulihan kepada para pihak yang berperkara ini berdasar pada Undang-Undang No.11 Tahun 2012 tentang Sistem Peradilan Pidana Anak dan Undang-Undang No.35 Tahun 2009 tentang Narkotika. Berdasarkan temuan dari putusan hakim didapati bahwa tujuan diterapkannya sistem peradilan pidana anak untuk bersama-sama mencari penyelesaian yang adil dengan menekankan pemulihan pada keadaan semula dan bukan pembalasan. Kegunaan: Pemerintah perlu membuat landasan hukum yang komprehensif untuk mengatur proses penyelesaian perkara penyalahgunaan narkotika pada anak berbasis keadilan restoratif secara simultan dan terintegrasi dalam pembaharuan undang-undang narkotika di Indonesia masa mendatang. Kebaruan: Dasar hukum terbaru dalam proses penyelesaian perkara penyalahgunaan narkotika berdasar keadilan restoratif yang dikaitkan Undang-Undang No.11 Tahun 2012 tentang Sistem Peradilan Pidana Anak dan Undang-Undang No.35 Tahun 2009 tentang Narkotika. Berdasarkan ketentuan tersebut akan dibahas lebih lanjut terkait proses penyelesaian perkara pidana berbasis konsep keadilan restoratif dengan memberikan penetapan diversi kepada anak.  Keywords: Penyalahgunaan, Narkotika, Keadilan Restoratif dan Anak